Local Legal Strategies to Increase Vaccination During the COVID-19 Pandemic — Lessons from New York City. Issue 3 (2022) - Landau, Lisa; Stark, Naomi; Chokshi, Dave A.
Abstract: Vaccine mandates played a critical role in the success of New York City's COVID-19 response. By relying on evidence as a substantive basis for the mandates and adhering to procedural requirements and precedent, New York City leveraged its position and expertise as a local governmental authority to devise mandatory vaccine policies that withstood numerous legal challenges. New York City's experience highlights the role of municipal government in mounting a meaningful public health response, and the strategies adopted by NYC may provide a blueprint for municipalities around the world facing the ongoing COVID-19 pandemic and the threat of future public health emergencies.